EFEKTIVITAS SEKOLAH RUJUKAN TERHADAP PENINGKATAN MUTU PADA JENJANG PENDIDIKAN MENENGAH - Nauraida, Indah Dwi (Universitas Negeri Surabaya, 2023)
Referral schools are schools that have been fostered and have met the National Education Standards (SNP) and have developed excellent programs in line with the school's potential and community needs and have achievements in both academic and non-academic fields. This study aims to describe how the effectiveness of the referral school towards improving the quality of education in SMA N 1 Srengat. The method used in this research is descriptive quantitative. The population of this study were residents of SMA N 1 Srengat including educators, education staff and students. Samples were taken using quota sampling totaling 50 people. The data collection technique in this study used a questionnaire and then processed using a percentage analysis technique. The results of the study revealed that the government's referral school program at SMA N 1 Srengat had been running effectively in tandem with the efforts to improve the quality of education. These results indicate that SMA N 1 Srengat has succeeded in improving the quality of education as an effort to help the government in the success of the referral school program. Key words: Effectiveness; Referral schools; Quality improvement